PELAKSANAAN TUGAS UNIT PENGELOLA LAPORAN HARTA KEKAYAAN PENYELENGGARA NEGARA (LHKPN) DI PEMERINTAH KOTA PEKANBARU TAHUN 2018 - Siti Wahyuni; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
LHKPN is the submission of wealth reports by state officials to the Komisi Pemberantasan Korupsi (KPK) Indonesia. LHKPN functions as a control tool and a mechanism to assess the honesty and integrity of the state administrators. The implementation of LHKPN in Pekanbaru, in accordance with Peraturan Walikota Pekanbaru Nomor 141 Tahun 2018 tentang Laporan Harta Kekayaan Penyelenggara Negara di Lingkungan Pemerintah Kota Pekanbaru, has started to implement LHKPN since 2017 by establishing the LHKPN task unit. The manager of the LHKPN program in Pekanbaru is the team that manages and coordinates the LHKPN with the establishment of an LHKPN Management Unit which is stipulated by a Mayor’s Decree. The secretariat of the LHKPN Management Unit is located at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Pekanbaru.     The purpose of this study was to see the implementation of the tasks of the Pekanbaru LHKPN Management Unit and to see the obstacles experienced in the implementation of the LHKPN in Pekanbaru. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques with primary data collection in the form of field interviews and secondary data collection in the form of documentation and literature study.     The results showed that all LHKPN implementation was carried out by the Komisi Pemberantasan Korupsi (KPK) and carried out directly by the leadership of the relevant government institution. The implementation of LHKPN has a legal basis Undang-Undang Nomor 28 Tahun 1999 tentang Penyelenggara Negara yang Bersih dan Bebas dari Korupsi, Kolusi dan Nepotisme. In the Pekanbaru, the implementation of the LHKPN is carried out by a task unit under BKPSDM Pekanbaru. The duties of the Pekanbatu LHKPN Unit are carried out based on Peraturan Walikota Pekanbaru Nomor 141 Tahun 2018 tentang Laporan Harta Kekayaan Penyelenggara Negara di Lingkungan Pemerintah Kota Pekanbaru. The obstacles experienced in carrying out LHKPN tasks in Pekanbaru are because of too weak administrative sanctions, low levels of awareness of LHKPN reporting, limited facilities and infrastructure and busy government officials. Keywords: LHKPN, BKPSDM, LHKPN Unit Performance.